Evaluation of stingless bee honey from Heterotrigona itama Cockerell as anti-obesity agent in high fat diet-induced obesity Sprague-Dawley rat model - Mohd Rafie, Ahmad Zulkifli (2017)
Heterotrigona itama is a common stingless bee species of Malaysia. However, studies on the health benefits of its honey are relatively limited compared to other stingless bee species of the world. In this study, the anti-obesity properties of stingless bee honey from H. itama were evaluated based on the weight changes, biochemistry parameters and morphological structures in diet-induced obese rat model. 56 male Sprague Dawley (SD) rats were induced with formulated high fat diet (HFD) to become obese, indicated by the value of 0.68 g/cm2, for 6 weeks. Then, treatment phase was carried out for the next 6 weeks. At the end of the experiment, rats were euthanized and their blood and organs (liver, aorta and adipose tissue) were sampled. Results showed significant reduction in percentages of body weight gain and adiposity index in groups treated with all the three dosages of stingless bee honey with percentages of body weight gain of 12.0 ± 3.1, -2.3 ± 2.9 and 11.1 ± 4.6 and adiposity index of 5.6 ± 0.3, 4.6 ± 0.5 and 6.8 ± 0.8, for 1000 mg/kg, 750 mg/kg and 500 mg/kg supplementations, respectively, compared to the control obese group with excess of percentage of body weight gain of 33.7 ± 2.8 and adiposity index of 10.1 ± 0.5. For the biochemistry analysis based on blood serum, levels of liver enzymes (ALT, AST and alkaline phosphatase) were significantly lower in all treated groups with 1000 mg/kg showing 51.0 ± 4.9, 154.5 ± 19.0 and 104.2 ± 25.5, 750 mg/kg showing 56.3 ± 5.6, 183.3 ± 18.0 and 122.0 ± 9.3, and 500 mg/kg showing 64.8 ± 8.6, 206.3 ± 18.9 and 140.5 ± 9.0, respectively. Lipid profiles of (triglycerides and LDL-cholesterol) were also significantly lower in all treated groups with 1000 mg/kg showing 0.73 ± 0.08 and 0.17 ± 0.061, 750 mg/kg showing 0.83 ± 0.08 and 0.12 ± 0.031, and 500 mg/kg showing 0.78 ± 0.08 and 0.17 ± 0.021, respectively, compared to control obese group which showed 1.33 ± 0.22 and 0.70 ± 0.132, respectively. Level of HDL-cholesterol in treated groups was significantly higher with 1000 mg/kg showing 1.33 ± 0.10, 750 mg/kg showing 1.35 ± 0.09, and 500 mg/kg showing 1.30 ± 0.09, compared to control obese group which showed 0.93 ± 0.11. Based on morphological structures, adipocyte size was smaller and hepatocytes were less ruptured in treated groups compared to untreated groups at 40× magnification. Histology results of aorta in treated groups directly mimic to the normal-like structure, compared to untreated groups. As a conclusion, the intervention study suggested that administration of stingless bee honey was successful to reduce the complication risks related to obesity such as liver disease. Our study also suggests that stingless bee honey possesses hepatoprotective action that could be used to control obesity by regulating lipid metabolism.